2016
DOI: 10.1242/jeb.137638
|View full text |Cite
|
Sign up to set email alerts
|

How moths escape bats: predicting outcomes of predator-prey interactions

Abstract: What determines whether fleeing prey escape from attacking predators? To answer this question, biologists have developed mathematical models that incorporate attack geometries, pursuit and escape trajectories, and kinematics of predator and prey. These models have rarely been tested using data from actual predator-prey encounters. To address this problem, we recorded multi-camera infrared videography of bat-insect interactions in a large outdoor enclosure. We documented 235 attacks by four Myotis volans bats o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 55 publications
(75 reference statements)
3
58
0
Order By: Relevance
“…S2, S3). Despite the very different initial state of of kinematic parameters during last-ditch evasive flight (Corcoran & Conner, 2016. Our 292 observations are further supported because the reaction of a given species was independent of whether 293 individuals were flying or not at stimulus onset.…”
Section: Results 213supporting
confidence: 56%
See 1 more Smart Citation
“…S2, S3). Despite the very different initial state of of kinematic parameters during last-ditch evasive flight (Corcoran & Conner, 2016. Our 292 observations are further supported because the reaction of a given species was independent of whether 293 individuals were flying or not at stimulus onset.…”
Section: Results 213supporting
confidence: 56%
“…We studied size as one explanatory 81 variable underlying potential species-specific differences in evasive flight, since size is positively 82 correlated with acceleration in a butterfly (Berwaerts, Van Dyck, & Aerts, 2002), and negatively 83 correlated with manoeuvrability in insects (Dudley, 2002). We use vertical flight strength as proxy for 84 flight speed, which, like many other variables, increases when moths actively perform last-ditch 85 evasive flight (Corcoran & Conner, 2016. Even though tethered flight does not allow us to 86 study actual 3D-flight behaviour, measurements of flight strength and its temporal variation do reveal 87 species-specific strategies for and interspecific differences in evasive flight.…”
Section: Introduction 37mentioning
confidence: 99%
“…Since the A2 cell threshold was exceeded at 1.4 m bat–moth distance, only moths with comparably long reaction times (>203 ms) would not initiate any last‐ditch manoeuvre. If moths were able to initiate a last‐ditch manoeuvre, power dives or other downward‐directed flight manoeuvres might prove most effective, since barbastelles mostly attacked from below and escape trajectories towards the bat are most successful (Corcoran & Conner, ). Even if the moth just initiated a last‐ditch manoeuvre, however, bats might still be able to catch it with their wing (wingspan about 25–28 cm; Rydell & Bogdanowicz, ).…”
Section: Discussionmentioning
confidence: 99%
“…lacking airflow and self‐motion) and their flight behaviour (Taylor, ). Although free‐flight experiments will be required to link vertical flight strength in tethered flight to actual three‐dimensional flight trajectories, free‐flight studies showed a clear change of kinematic parameters during last‐ditch evasive flight (Corcoran & Conner, , ). Our observations are further supported because the reaction of a given species was independent of whether individuals were flying or not at stimulus onset.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed wing surface area as one size‐related explanatory variable underlying potential species‐specific differences in evasive flight. We used vertical flight strength as proxy for flight speed, which, like many other variables, increases when moths actively perform last‐ditch evasive flight (Corcoran & Conner, , ). Even though tethered flight does not allow us to study actual 3D flight behaviour, measurements of flight strength and its temporal variation revealed species‐specific strategies, and corresponding interspecific differences, in evasive flight.…”
Section: Introductionmentioning
confidence: 99%